DESCRIPTION OF PERSONAL PROTECTIVE EQUIPMENT USED OBEDIENCE IN WASTE PROCESSING WORKERS OF DR. SOEGIRI HOSPITAL - Lailiyah Mukhadiroh; Erwin Dyah Nawawinetu (Journal of Industrial Hygiene and Occupational Health, 2019)
The use of Personal Protective Equipment (PPE), is a way to control and reduce the risk of accidents. Worker of waste processing facility was handling the election process until destruction that can cause various diseases when not using PPE. The general objective of this research wa to study the description of the factors that related to PPE using compliance in waste processing workers in Dr Soegiri Hospitals. This study was an observational study. 7 workers who do waste processing in Dr Soegiri Hospitals was the population study. The studied variables were described of the relationship between knowledge, attitude, availability of PPE, PPE accessibility, training in the use of PPE, supervision, warning, punishment with compliance in using PPE. Results showed that the respondents have good knowledge and had a positive attitude, PPE was available, easy PPE accessibility, partly following a training in using PPE, was not routinely given a warning, never get punishment but only warning, most of the respondents use the PPE. Respondents who had knowledge and a good attitude, had good compliance in the use of PPE. Availability of PPE was complete and easy accessibility, but not all the respondents always comply to used PPE and respondents who received training more than once tend to be more comply. In a regular monitoring, the compliance of the respondents in the use of PPE tend to be better. Respondents who did not often reprimanded then had higher compliance and all respondents has never gotten punishment. The conclusion was the predisposing, enabling and reinforcing could give reinforcement in PPE use (compliance). Based on the research results expected that always using PPE needed, as well as management were suggested for training and increase surveillance that can motivate workers in the use of PPE.Keyword: personal protective equipment; compliance; hospital waste